2008
DOI: 10.1291/hypres.31.289
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Incident Ischemic Stroke in Hospitalized Heart Failure Patients: A Pilot Study

Abstract: Stroke is sometimes seen in patients with congestive heart failure (CHF). The factors that best predict incident stroke in hospitalized CHF patients are not well known. We performed this pilot study to explore the clinical markers of incident stroke in CHF patients. We studied 111 hospitalized patients with CHF (mean age, 67 ± 11 years). Ambulatory blood pressure (BP) monitoring, blood tests, and echocardiography were performed in these patients just before they left the hospital, and all cardiovascular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Abnormalities of hemostasis, blood constituents, and endothelial dysfunction are considered the mechanism of ischemic stroke onset in patients with heart failure [16]. Previous report demonstrated that high plasma BNP was independent predictor of stroke event in hospitalized congestive heart failure patients [17]. Therefore, congestive heart failure may induce ischemic stroke in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of hemostasis, blood constituents, and endothelial dysfunction are considered the mechanism of ischemic stroke onset in patients with heart failure [16]. Previous report demonstrated that high plasma BNP was independent predictor of stroke event in hospitalized congestive heart failure patients [17]. Therefore, congestive heart failure may induce ischemic stroke in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, congestive heart failure may induce a cardioembolic stroke. A previous report demonstrated that high plasma BNP was an independent predictor of a stroke event in hospitalized congestive heart failure patients (14). Moreover (17), hypertrophic cardiomyopathy (18), pulmonary embolism (19), and Takotsubo cardiomyopathy (20) (22,23).…”
Section: F I G U R E 1 Me a N ± S D P L A S Ma B Np L E V E L S A Nmentioning
confidence: 95%
“…Many retrospective studies have been conducted to identify the effect of nocturnal hypertension and non-dipping patterns on its clinical implications. Nocturnal hypertension is a risk factor for target organ damage for the brain, heart, kidney, and large and small arteries and for all CVD events including both hemorrhagic and ischemic stroke, CHD, HF (especially with HF with preserved ejection fraction), CKD, and sudden cardiac death, independently of clinic BP, in general populations and hypertensive patients 6)20)50)51). In the PAMELA study, the risk of cardiovascular death for each 10 mmHg increase of systolic BP progressively increased from office to home, day, 24-hour to night BP values 52).…”
Section: Clinical Significance Of Nocturnal Hypertensionmentioning
confidence: 99%